2008
DOI: 10.1111/j.1471-6712.2007.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies and styles of family carers of persons with enduring mental illness: a mixed methods analysis

Abstract: A qualitative exploratory study investigated the experiences and needs of family carers of persons with enduring mental illness in Ireland. The current mixed-methods secondary study used content analysis and statistical procedures in order to identify and explore the coping strategies emerging from the original interviews. The majority of family carers reported use of active behavioural coping strategies, sometimes combined with active cognitive or avoidance strategies. The percentage of cares reporting use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 27 publications
4
21
0
1
Order By: Relevance
“…For most variables, our results align with several other studies in this field [8,9,13,15,32]. Nevertheless, the caregivers in this study were less likely to have the perception that the patient was at fault or that they themselves were responsible for the onset of the illness than compared to the results published by Lobban and collaborators [5].…”
Section: Resultssupporting
confidence: 89%
“…For most variables, our results align with several other studies in this field [8,9,13,15,32]. Nevertheless, the caregivers in this study were less likely to have the perception that the patient was at fault or that they themselves were responsible for the onset of the illness than compared to the results published by Lobban and collaborators [5].…”
Section: Resultssupporting
confidence: 89%
“…However, mental health professionals could facilitate and speed up this process by supporting the families emotionally. The present study showed that talking to others was a valuable strategy in managing the consequences of having a family member with BD, consistent with the findings of the study by Kartalova‐O'Doherty and Doherty (2008). However, our findings, in line with those of Schröder et al .…”
Section: Discussionsupporting
confidence: 92%
“…In this case, individuals do not share their burdens; it is difficult for them to ask for help, and if they do, there is no guarantee they will receive it (Kellezi & Reicher, ; Stevenson, McNamara, & Muldoon, ). This might also result in one or several family members employing avoidance strategies to cope (i.e., avoiding conversation about the illness and avoiding contact with the relative), therefore impacting family relationships (Kartalova‐O'Doherty & Doherty, ).…”
Section: Discussionmentioning
confidence: 99%